MITOS DAN RITUS : Suatu Refleksi Filosofis - Snijders, Adelbert (LOGOS, 2007)
Cultural Anthropology distinguishes ‘primitive cultures’ and ‘civilized cultures’. It is difficult to find an objective criterion to justify this distinction but the difference is commonly accepted. However man - in primitive or in civilised cultures – is a metaphysical being, who asks metaphysical questions. As ‘Logos’ man is open to the reality revealing itself to man and open to truth. Metaphysics of ‘primitive people’ is expressed in myths and mythological tales. Metaphysics ‘civilised peoples’ is systematic, scientific, expressed in concepts and definitions. Both kinds of metaphysics may be called ‘rich and poor’. They need each other and enrich each other. There is an important connection between myths and rites. It is very important recognizing ‘the primitive’ as a metaphysical being in other to understand the myths. However, ‘the cultural situation’ is also important. There are several kinds of primitive cultures and myths. From the side of their economical situation we distinguish food-gatherers (not specialised) and specialised hunters, pastoralists and cultivators. The metaphysics of the food gathers and pastoralists is theistic (food-gathers) or deistic (pastoralist). Their metaphysics is dominantly Transcendent. The Metaphysics of the cultivators is cosmo-biological and dominantly Immanent. The way of live of the hunters is often characterised as a kind of technical magic.